The Role of Religious Education in Shaping Human Development in Cameroon - Giyoh Gideon Nginyu; Kebuya Nathaniel Nganchi (Research and Advances in Education, 2024)
This study investigated the effect of religious education on human development in Cameroon. The data were analysed quantitatively using regression analysis, specifically employing the Tobit model due to the censored nature of the dependent variable, which had limits on its range. The findings revealed that religious education significantly enhances moral reasoning, civic engagement, and resilience among youth. However, the systemic marginalisation of religious knowledge within formal education limits its potential benefits. These findings highlight the complex interplay between religious education and human development, suggesting both potential benefits and challenges in the Cameroonian context. The study recommends integrating religious education into the school curriculum to foster ethical behavior and community involvement, ultimately contributing to sustainable development in Cameroon.